Open Loop Recycling of Recycled Polypropylene for Motorcycle Saddle Application - Piyachat Wattanachai; Benjawan Buasathain; Christian Antonio; Susan Roces (Department of Chemical Engineering, Universitas Gadjah Mada, 2018)
This research investigated the possibility of using polymer blends of virgin andrecycled polypropylene (PP) for a motorcycle saddle application. Three differentrecycled PPs obtained from different sources contained carbon black (CB). Specimenswere prepared by injection molding for mechanical property testing and colorcharacterization whereas scraps from runners were used for thermal property testing. Itwas found that tensile and flexural properties of recycled PPs were better than those ofvirgin PP due to the fact that recycled PPs contained CB which is a reinforcing material.These properties were improved as the amount of recycled PP added increased. Sincerecycled PPs are strong materials, they are hence brittle resulting in lowering impactstrength and percent elongation. The recycled PP sources and compatibility betweenvirgin and recycled PPs strongly influence the blends' properties. The melt flow index ofthe blends increased as the amount of the recycled PP increased because of the shortpolymer chains of recycled PP resulting from earlier processing. Blending virgin PP withrecycled PP not only improves its properties, but also reduces raw material costs in therange of 5-13%. The advantage of open loop recycling is a wider recycled plasticmarket.